Multi-Scale Ecological Connectivity Dynamics Associated With Hydropower Station: A Case Study in the Lancang River Valley - Liu, Shiliang; Wang, FangFang; Deng, Li; Dong, Yuhong; Liu, Yixuan (Frontiers in Ecology and Evolution, 2021)
Dam construction is a major threat to terrestrial ecological processes that exhibit spatial variation. As an effective indicator of species movements at large scales, the dynamics of forest landscape connectivity for the dispersal abilities of local species such as primates both upstream and downstream of the Manwan hydropower station were compared in three periods: before, during, and after dam construction (in 1974, 1988, and 2004, respectively). The equivalent connected area (ECA) index which was modified from the probability of connectivity (PC) index based on the graph theory was applied in this study. We used this method to analyze the spatial and temporal changes in the overall forest landscape connectivity due to dam construction. The results showed that forest connectivity decreased after dam construction. The forest connectivity upstream was much greater than that downstream in 1974 but was lower in 1988 and 2004. The importance of connectivity increased with increasing dispersal distance. Only 8, 12, and 18% of forest patches of small area exhibited changes in 1974, 1988, and 2004, respectively. Most of the large habitat patches (i.e., those with dECA values >50%) remained stable, and the greatest patch changes were found at a dispersal distance of 400 m in all three periods. These large forest patch changes often occurred near the boundary of the study area. The Betweenness Centrality indicator, which identifies patches as stepping stones while accounting for ecological processes and biological flows at a larger scale, indicated that some habitat patches near Manwan Dam acted as stepping stones in maintaining the forest connectivity. Furthermore, rank correlations between the forest patch area and the three dPC (intra, flux, connector) fractions indicated that the dPCflux indicator can be used to measure the prioritization of habitat patches.